Detection of enzymatic levels in patients with thalassemia in Dewanyah province (Journal of Pharmaceutical Negative Results, 2022)
This study deals with the knowledge of the relationship and the negative impact of thalassemia disease on liver function. The study included 60 children with thalassemia in the age group (2-14) years, and the study included 20 children as a control group and in the same age group. The study included measuring liver function represented by measuring the activity of liver enzymes. The current study aimed to find the immune differences for people with thalassemia anemia in Al-Diwaniyah Governorate, where samples were collected from pathological analysis laboratories in Al-Diwaniyah hospitals. They were randomly selected with gender and age proportional to the group of patients, and patient groups and control groups were distributed as follows (31 males and 29 females) for patients and (10 males 10 females) for the control group. The current study examined the differences in the effect of sex on the average concentrations of components in the blood serum at a probability level of 5% in the serum of thalassemia patients. Liver enzymes were included in the study of GOT enzyme and were for ages 2-5 years (25.6±17.6), age 6-9 years (25.9±6.93), and age 10-14 years (28.5±8.61) without significant difference, and GPT enzyme also did not appear. Any significant difference between the age groups was determined for ages 2-5 years (14.2±21), ages 6-9 years (17.25±8.46), and ages 10-14 years (25.52±3.76). In the same study context, it was found that the glucose concentration was not significant for age groups, as it was 2-5 years old (123±5.94), 6-9 years old (120.6±4.43), and 10-14 years old (122.9±5.7), although it was significantly higher with the healthy control group.